Use of Preoperative CHA2DS2‐VASc Score to Predict the Risk of Atrial Fibrillation After Cardiothoracic Surgery: A Nested Case–Control Study from the Atrial Fibrillation Suppression Trials (AFIST) I, II, and III. Issue 5 (21st March 2013) - Baker, William L; Coleman, Craig I.; White, C. Michael; Kluger, Jeffrey
<x xml:space="preserve">Abstract</x> Study Objective To evaluate whether the preoperative CHA2DS2‐VASc score predicts the risk of atrial fibrillation (AF) after cardiothoracic surgery (CTS). Design Retrospective, nested case–control study. Patients A total of 560 patients undergoing coronary artery bypass grafting and/or valvular surgery from the Atrial Fibrillation Suppression Trials I, II, and III. Measurements and Main Results All variables showing a univariate association (p≤0.20) with AF occurrence were entered into a backward stepwise multivariate logistic regression analysis to control for potential confounders and to calculate adjusted odds ratios (AORs) with 95% confidence intervals (CIs). The population was age 67.8 ± 8.6 (mean ± SD) years and 77.1% male, with CHA2DS2‐VASc scores of 0–1 (low) in 34 patients (6.1%), 2–3 (medium) in 261 patients (46.6%), and more than 3 (high) in 265 patients (47.3%). Post‐CTS AF occurred in 177 patients (31.6%), with 27%, 23%, and 41% in the low–, medium–, and high–CHA2DS2‐VASc score groups, respectively. The high‐score group had a 2.3‐fold increased odds of developing AF versus the medium‐score group (p<0.0001). The differences between the high‐ and medium‐score groups when each group was compared with the low‐score group were not statistically significant. On the multivariate logistic regression analysis, CHA2DS2‐VASc score was associated with development of AF (AOR 1.20, 95% CI 1.06–1.36). Conclusion Increasing CHA2DS2‐VASc score was an independent predictor for the development of post‐CTS AF, with patients in the high‐score group having the highest overall incidence.